Association of TMAO levels with indicators of ulcerative colitis activity - Yelena Laryushina; Nadezhda Samoilova-Bedych; Lyudmila Turgunova; Alexander Marchenko; Yermek Turgunov (Babol University of Medical Sciences, 2025)
Background: The diagnosis of ulcerative colitis (UC) today is limited to a small number of biomarkers. Trimethylamine-N-oxide (TMAO) is the product of reactions resulting from the degradation of dietary-free choline, phosphatidylcholine, and carnitine metabolism by the intestinal microbiota. Earlier studies showed his involvement in the pathogenesis of UC. To study the association of TMAO with clinical, laboratory, and endoscopic indicators of UC activity. Methods: an observational cross-sectional comparative study was conducted based on the NCJSC "KMU" clinic, Karaganda, Kazakhstan. High-performance liquid chromatography measured TMAO concentration in 63 patients with UC (age Me 37 (30-52) and 38 healthy individuals (age Me 38 (28.5-49.5). Results: Median TMAO level in patients with UC-0.286 μmol/l was significantly lower than in the control group Me 0.646 μmol/l (p<0.0001). TMAO had significant differences in groups with clinically active and inactive colitis (P=0.003). TMAO correlated with disease activity by Montreal scale (r=-0.389, P=0.002) and severity of attack by Truelove-Witts (r=-0.301, P=0.027 respectively), patient's age (r=0.377, P=0.003), stool frequency (r=-0.427, P=0.001); laboratory parameters: WBC (r=-0.31, P=0.042), blood albumin (r=0.379, P=0.002) and fecal calprotectin (r=-0.314, P=0.022). TMAO did not differ between groups divided by the extent of the pathological process and endoscopic activity. Conclusion: in patients with UC, TMAO levels decrease compared with healthy individuals and differences in groups depend on the disease activity. These results give reason to consider changes in TMAO levels as a potential marker of UC and the severity of its course.